Influence of air–water two-phase flow on the performance of a high-speed inducer. (December 2020) - Cui, Baoling; Cai, Mingzhe; Li, Yifan
This study is to reveal the influence of incoming flow containing air on the internal flow and performance of a high-speed inducer. Numerical calculations were performed herein under different air volume fraction conditions based on the shear-stress transport turbulence model and the Eulerian–Eulerian heterogeneous flow model. The external characteristic, cavitation performance and visualization experiment were conducted under the air–water two-phase condition. As a result, the effect of incoming flow containing air under small flow rate condition on the decline of the inducer head was larger than that under large flow rate condition. The proper air volume fraction was beneficial to the improvement of the inducer cavitation performance. As the air volume fraction increased, the pressure gradients in the axial and radial directions of the inducer gradually reduced and the supercharging performance of the inducer also worsened. The flow near the hub in the flow channel became messy, and the turbulence energy increased. The air mainly concentrated in the leading edge rim and the low blade height region near the hub in the flow channel. The air expanded in the circumferential, radial and axial direction as the air volume fraction increased.